How would a permanently Refundable Child and Dependent Care Credit affect eligibility, benefits, and incentives? - Gabrielle Pepin (W.E. Upjohn Institute for Employment Research, 2021)
The federal Child and Dependent Care Credit (CDCC) subsidizes child care costs for working families. Before 2021, the CDCC was nonrefundable, so only families with positive tax liability after other deductions benefited. I estimate how CDCC eligibility, benefits, and marginal tax rates would change if the credit were made permanently refundable, relative to 2020 CDCC parameters set to be restored in 2022. Under refundability, some 5 percent of single parents gain eligibility and receive on average over 1,000 annually. Eligibility increases are largest among Black and Hispanic households. Increases in marginal tax rates among moderate-income taxpayers are small.
Keywords: H24; J13; J22; 330; Child and Dependent Care Credit; marginal tax rates; eligibility; refundability